The Construction of an AI-Based Curriculum and Learning Management System in Rural Private Madrasah Ibtidaiyah in Indonesia - Mulyono Mulyono (Nadwa: Jurnal Pendidikan Islam, 2025)
The era of digitalization demands technological adaptation across all sectors of education, including Islamic private school (Madrasah Ibtidaiyah/MI) in Indonesia. This study aims to construct a contextual Artificial Intelligence (AI)-based curriculum and learning management system for rural private MI. The research employs mixed methods sequential explanatory design, integrating a Systematic Literature Review (SLR) and a single qualitative case study conducted at the pilot MI Ulul Albab in Prayungan Village, Sawoo, Ponorogo. Data were collected through literature review, in-depth interviews with the principal and teachers, and field observations. The findings reveal a significant gap between the theoretical potential of AI in education and the realities of limited digital infrastructure in rural madrasahs. Nevertheless, the urgency of AI adoption remains high, particularly in supporting teachers’ administrative tasks and facilitating more personalized learning. Infrastructure constraints are partially offset by the strong enthusiasm and local agency of school leaders and teachers. Based on these findings, this study proposes the concept of “Adaptive Innovation Based on Local Agency,” an approach that emphasizes mobile-first, lightweight, and low-cost AI solutions.